Meningkatkan Kemampuan Literasi Siswa Sekolah Dasar Melalui Permainan Estafet Kata - Rizky Pratama; Sutejo Sutejo; Mudopar Mudopar; Rahmad Khodari (Universitas Pakuan, 2026)
Improving Elementary School Students' Literacy Abilities Through Word Relay Games Literacy is a basic skill that elementary school students must master to support the learning process in various fields. However, many students still face difficulties in reading and understanding texts effectively. One contributing factor is learning methods that are less interesting and not interactive. Therefore, innovations in literacy learning are needed, one of which is through the Estafet Kata game. This method is thought to be able to effectively increase students' interest and literacy skills through fun and collaborative activities. This study used an experimental method with a pretest-posttest control group design. The research subjects consisted of two groups of elementary school students: the experimental group who used the Estafet Kata game and the control group who learned using traditional methods. Data were collected through literacy tests before and after treatment, observations during the learning process, and questionnaires to determine student responses. Data analysis was carried out using statistical methods to see differences in learning outcomes between groups. This study is expected to result in a significant increase in students' literacy scores in the experimental group.